Towards a Post-Covid Global Financial System Lessons in Social Responsibility from Islamic Finance. - Hassan, Kabir; Aishath Muneeza; Sarea, Adel, 1979- (Emerald Publishing Limited, 2022)
In Towards a Post-Covid Global Financial Systema team of experts explore how COVID-19 has affected the most vulnerable parts of the global economy; how it has been met by Islamic banking and finance; and how the principles of Islamic social finance could be used to have a fairer, more resilient Islamic finance system for all.